Quotations for occasions - Knowles, Elizabeth (Elizabeth M.) (Glasgow : Collins, 2008)
A treasury of quotations coupled with a unique and insightful look at language; the perfect gift for language lovers and an essential reference for anyone looking for the right words to say. Whether you're making a speech, offering congratulations or condolences, or simply hold an interest in language, Elizabeth Knowles' insightful selection of quotations will provide inspiration. Elizabeth Knowles has long been considered an authority on quotations. Here she provides a playful, humorous look at a range of themed quotations, exploring how language and opinions have changed over time. This highly browsable, witty guide to quotations offers practical help as well as being a joy to read and explore.
Includes indexes.
Keywords: Quotations, English